Cyclic cryotherapy with vitamin D facilitates early rehabilitation after total knee arthroplasty - Li, Fulin; Mo, Yingrong; Huang, Xiao; Sun, Ke; Li, Baichuan; Yin, Dong (Frontiers in Medicine, 2024)
Objective: This study aimed to evaluate the efficacy of cyclic cryotherapy and vitamin D administration on early rehabilitation after total knee arthroplasty (TKA), as its efficacy remains unclear. Methods: We divided 150 patients (three groups) who underwent TKA into those treated with or without cyclic cryotherapy and vitamin D. Results: Compared with patients who did not receive cyclic cryotherapy, those who received postoperative cyclic cryotherapy and vitamin D supplementation had significantly higher American Knee Society Scores (AKSS) on postoperative day (POD) 7 and at 1 month postoperatively; higher visual analogue scale (VAS) values on POD1-3 and POD7; reduced thigh swelling on POD3 and POD7; increased range of motion (ROM) on POD3, POD7, and at 1 month postoperatively; and reduced postoperative length of stay (PLOS). However, no significant difference in patient satisfaction was observed between the patient groups. At 1 and 3 2 months postoperatively, patients administered cyclic cryotherapy and vitamin D had significantly higher AKSS, ROM, and vitamin D levels than those who did not receive vitamin D. No perioperative complications such as surgical site infection, skin frostbite, or vitamin D intoxication were observed. Conclusion: Cyclic cryotherapy post-TKA had short-term advantages in terms of AKSS, VAS, thigh swelling, ROM, PLOS, and accelerated rehabilitation, but did not improve patient satisfaction. Cyclic cryotherapy combined with vitamin D improved AKSS and ROM at 1 and 3 months postoperatively.